2012
DOI: 10.1007/s11099-012-0007-9
|View full text |Cite
|
Sign up to set email alerts
|

Grafting onto Cucurbita moschata rootstock alleviates salt stress in cucumber plants by delaying photoinhibition

Abstract: To determine how the use of a given rootstock can influence the functioning of the photosynthetic apparatus of the scion under salt stress, the growth, gas exchange, photosystem II (PSII) efficiency, xanthophyll cycle, and chloroplast ultrastructure of nongrafted, self-grafted, and pumpkin-grafted (hereafter referred to as rootstock-grafted) cucumber (Cucumis sativus L.) plants were investigated at day 15 after being treated with 90 mM NaCl. The reductions in plant growth of the rootstock-grafted plants were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 37 publications
1
8
0
3
Order By: Relevance
“…The present results agree with those obtained by Abd-Alla (2002); Liu et al (2012) and Rahmatian et al (2014) who reported that graft compatibility between rootstock and scion is the most important factor influencing the survival of grafted plants. Also, many investigators reported that cucumber plants grafted onto cucurbita ficifolia gave the highest percentage of successful grafted plants .…”
Section: -Effect Of Grafting and Some Foliar Applications On Vegetatsupporting
confidence: 93%
“…The present results agree with those obtained by Abd-Alla (2002); Liu et al (2012) and Rahmatian et al (2014) who reported that graft compatibility between rootstock and scion is the most important factor influencing the survival of grafted plants. Also, many investigators reported that cucumber plants grafted onto cucurbita ficifolia gave the highest percentage of successful grafted plants .…”
Section: -Effect Of Grafting and Some Foliar Applications On Vegetatsupporting
confidence: 93%
“…And with regard to increased qP, carboxylation of plant promoted ATP production and improved the rate of consumption in non-cyclic electron transport process. The decrease in F v 0/F m 0 under chilling stress was attributable to the increased excitation energy quenching by PSII antennae and catalytic cycle of cytochrome P450 (Liu et al 2012;Xia et al 2009a;Wu et al 2014). Demmig-Adams et al (1996) reported that absorbed photon energy in plant can be divided into three parts, photon energy absorbed by PSII antennae and trapped by closed PSII reaction centers (E), absorbed photon energy that is thermally dissipated (D) and photon energy absorbed by PSII antennae trapped by open PSII reaction centers (P).…”
Section: Discussionmentioning
confidence: 95%
“…The PN clearly decreased at low temperature but was enhanced by mycorrhiza both at ambient and at low temperature similarly. Decreased CO2 assimilation can be caused by stomatal limitation or by nonstomatal factors (Begcy et al 2012, Liu et al 2012, Shu et al 2014, Zhang et al 2009: CO2 assimilation is primarily limited by gs if accompanied by a decrease in gs and Ci. On the other hand, if gs decreases but Ci does not change or increases, the decrease in CO2 assimilation should be ascribed to nonstomatal factors.…”
Section: Discussionmentioning
confidence: 99%